2016
DOI: 10.1016/j.jtho.2015.12.108
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Clinical Prediction Model for Prognosis in Malignant Pleural Mesothelioma Using Decision Tree Analysis

Abstract: We have developed and validated a simple, clinically relevant model to reliably discriminate patients at high and lower risk of death using routinely available variables from the time of diagnosis in unselected populations of patients with MPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(118 citation statements)
references
References 33 publications
3
108
2
5
Order By: Relevance
“…The following scores are described in more detail below; the EORTC prognostic score (EPS), the CALGB score, 82–87 mGPS have been studied retrospectively in a cohort of patients with mesothelioma, 71 the LENT prognostic score 88 and a prognostic model using decision tree analysis was published by Brims et al 89 in 2016.…”
Section: Section 8: Factors Determining Prognosis and Timing Of Treatmentioning
confidence: 99%
See 1 more Smart Citation
“…The following scores are described in more detail below; the EORTC prognostic score (EPS), the CALGB score, 82–87 mGPS have been studied retrospectively in a cohort of patients with mesothelioma, 71 the LENT prognostic score 88 and a prognostic model using decision tree analysis was published by Brims et al 89 in 2016.…”
Section: Section 8: Factors Determining Prognosis and Timing Of Treatmentioning
confidence: 99%
“…Brims et al derived a prognostic model using classification and regression tree analysis from an unselected population of 482 patients newly diagnosed with MPM in Western Australia, of whom 274 were collected retrospectively and 208 prospectively 89 . Unlike the cohorts used to derive the CALGB and EORTC models, which were of participants in chemotherapy trials, this paper included all patients with a confirmed diagnosis of MPM within the inclusion period.…”
Section: Section 8: Factors Determining Prognosis and Timing Of Treatmentioning
confidence: 99%
“…Our data also included a higher proportion of patients not having chemotherapy (53% did not), and this differs to other previously published datasets. 4 This may be due to inclusion of patients from 2006, three years prior to pharmaceutical benefit schedule (PBS) approval to subsidize pemetrexed in the treatment of MPM. In the cohort of patients prior to this event, the majority of patients were aged older than 75, and this may explain why there was a higher rate of patients receiving best supportive care.…”
Section: F I G U R E 2 Examples Of Pd-l1 Staining In Tumor Tissuesmentioning
confidence: 99%
“…Older age, male gender and sarcomatoid histological subtypes have been shown to correlate with poor survival. 4 Epithelioid subtype has a median survival of 14.8 months, not classified subtype, 13.9 months, biphasic subtype 9.1 months, and 4 Clinical variable such as weight loss, anemia, hypoalbuminemia and platelet count are also other poor prognostic factors. 5 Expression of programmed death ligand 1 (PD-L1) has been studied in several tumors as a prognostic biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…It occurs most frequently in the pleura but may affect the peritoneum 1 2. Patients with mesothelioma have a high burden of symptoms,3 4 and median survival is less than 1 year 5. The UK and Australia have some of the highest death rates in the world from mesothelioma 6 7.…”
Section: Introductionmentioning
confidence: 99%